A Hybrid CFD-BEM Analysis of the Aerodynamic Performance of a Cut-Out Hollow Pipe Horizontal Axis Wind Turbine Blade - Tanguilig, Neil Richard P.; Danao, Louis Angelo M. (Science Diliman: A Journal of Pure and Applied Sciences, 2017)
This study investigated the performance of a cut-out hollow pipe blade profile in small horizontal axis wind turbines (HAWT). Although this type of blade was expected to have losses in eff iciency, such blade prof ile can be easily manufactured locally, and could potentially have a lower cost compared to conventional blades with aerofoil prof iles. Numerical simulations using Unsteady Reynolds Averaged Navier Stokes (URANS) were used to derive the aerodynamic characteristics of the cut-out hollow-pipe sections. The Blade Element Momentum (BEM) method was then used to investigate the performance of the HAWT’s rotor. Numerical results show that cut-out hollow-pipe sections have poor aerodynamic characteristics due to their simple geometry and crude design. BEM demonstrate that rotor with cut-out hollow pipe blades can still extract the kinetic energy of the wind but only at low tip speed ratios. Parametric studies show that the performance can be improved by altering the pitch of the blades and by adding additional blades to the rotor. Keywords: Wind energy, CFD, BEM, blade analysis, wind turbine, pipe blade